"First find your peasant ..." - Vale, Brenda; Shaw, Yvonne (Architectural History Aotearoa, 2019)
Within the context of Edwardian architecture, this paper concerns the interior of dwellings in the 1900s and in particular the furnishings and objects inspired by the Arts and Crafts movement that people might have chosen to have in their homes. The Arts and Crafts section of the 1906 International Exhibition in Christchurch included work by the Haslemere Peasant Arts Society and Haslemere Peasant Industries from England. This paper explores how this movement began, and speculates why its works were part of an exhibition that included works by well-known Arts and Crafts protagonists, such as Morris, Ashbee and Voysey. It looks at the figures involved in the Haslemere ventures, including Godfrey Blount, and the response in the New Zealand press to his ideas that at least 90% of workers should want less rather than more wages, and as a result be involved in working on the land (Blount "Religion and Riches" pp 91-93). The paper also speculates about the life of the peasant and the romanticised view taken of peasants by proponents of the Arts and Crafts movement. It also discusses whether the Arts and Crafts would have flourished, both in New Zealand and Britain, without societies with a middle-class wealthy enough to adorn their homes with its artefacts, or indeed wealthy enough to bankroll it.